2001
DOI: 10.1002/jnr.1219
|View full text |Cite
|
Sign up to set email alerts
|

Altered circadian cortisol secretion in Alzheimer's disease: Clinical and neuroradiological aspects

Abstract: We determined circadian salivary cortisol levels in 18 outpatients affected by probable Alzheimer's disease (AD) and looked for a possible correlation with both cognitive impairment and brain CT scan findings. The diagnosis of probable AD was made according to the NINCDS-ADRDA criteria. The severity of cognitive impairment was quantified using the Mini Mental State Examination (MMSE) and the Global Deterioration Scale (GDS). Cortisol levels were measured on saliva samples collected at 08:00 AM and 08:00 PM. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 30 publications
1
50
1
2
Order By: Relevance
“…A dysregulation of cortisol secretion pattern has been associated with different pathologies [16,19]. This study reports that CM appears not to be associated with impairment of circadian variation of cortisol and DHEA-S: the physiological rhythm was maintained in all the subjects, with morning levels significantly higher than in the evening.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A dysregulation of cortisol secretion pattern has been associated with different pathologies [16,19]. This study reports that CM appears not to be associated with impairment of circadian variation of cortisol and DHEA-S: the physiological rhythm was maintained in all the subjects, with morning levels significantly higher than in the evening.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies from our group and others showed that saliva allows an easy, stress-free means for monitoring changes of adrenal function in physiological and pathological conditions [8][9][10][11][16][17][18]. The cortisol, DHEA-S and testosterone levels, and accordingly, the cortisol/DHEA-S and testosterone/cortisol ratios, obtained from the saliva appear to be more reliable measurements because salivary levels reflect better than those in plasma the hormone serum fraction that is biologically active [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol dysregulation is commonly found in patients with Alzheimer disease (AD) [1][2][3][4][5] and has been related to AD pathology in animals and humans. 4,[6][7][8][9][10] In rodent models, glucocorticoid increases have preceded b-amyloid (Ab) plaques and tau phosphorylation (for review, see references 7 and 8).…”
mentioning
confidence: 99%
“…Cross-sectional studies reveal that sleep disturbances are associated with memory and cognitive impairment. Clinical studies in AD patients favour disruption of the circadian timing system in AD since numerous overt rhythms including body temperature, glucocorticoid, melatonin and other hormonal rhythms are disturbed [67][68][69]. Phase differences between the rest-activity and core body temperature cycles are significantly delayed in AD patients [70].…”
Section: Sleep-wake Rhythm and Circadian Rhythm Disturbances In Alzhementioning
confidence: 99%